1987
DOI: 10.1051/apido:19870403
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of Varroa Jacobsoni During Successive Brood Cycles of the Honeybee

Abstract: SUMMARYNewly capped worker brood cells were numbered on a sheet of transparent plastic, temporarily attached to the top bar using two thumbtacks. Into each cell an adult female Varroa mite was introduced. After ten days the cells were opened and the contents studied. Those females still present and alive were introduced into newly capped brood cells an so on.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
6

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 1 publication
0
51
0
6
Order By: Relevance
“…A wire gauze prevented the bees from removing the mites from the sheet. Ruijter, 1987 (Liebig, 1994;Boot et al, 1995;Mar-tin, unpublished data) that suggested a strong correlation between levels of falling mites and the emergence of honeybee brood. The level of mite drop from naturally infested worker cells was nearly twice as high as that from the drone cells, despite drone cells being more attractive to the mite (Fuchs, 1990 (Martin, 1994) (Nation et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…A wire gauze prevented the bees from removing the mites from the sheet. Ruijter, 1987 (Liebig, 1994;Boot et al, 1995;Mar-tin, unpublished data) that suggested a strong correlation between levels of falling mites and the emergence of honeybee brood. The level of mite drop from naturally infested worker cells was nearly twice as high as that from the drone cells, despite drone cells being more attractive to the mite (Fuchs, 1990 (Martin, 1994) (Nation et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…The cell caps of the control group were opened and closed in the same way, but no mites were placed inside. For reidentification the position of the cells was marked on a clear plastic sheet that could be readjusted to the same position (De Ruijter, 1987 (Jones and Rothenbuhler, 1964;Rothenbuhler, 1964 In 2 of 3 cells that were uncapped and containing live pupae after 6 days, several mites were found hiding at the cell bottom under the pupae. In one of these 2 cells we found 3 adult V jacobsoni, one egg, and 2 female deutonymphs.…”
Section: Methodsmentioning
confidence: 99%
“…These mites may be callow or have reproduced once or several times [26]. In addition these mites may have a different origin owing to transfer by drifting of drones or inexperienced forager bees [35,54], or by robber bees [53].…”
Section: Does Invasion and Reproduction Depend On The History Of The mentioning
confidence: 99%